Designing information human factors and common sense in information design - Katz, Joel, 1943- (John Wiley & Sons, Inc., 2012)
"Information Design shows designers in all fields - from user-interface design to architecture and engineering - how to design complex data and information for meaning, relevance, and clarity. Written by a worldwide authority on the visualization of complex information, this full-color, heavily illustrated guide provides real-life problems and examples as well as hypothetical and historical examples, demonstrating the conceptual and pragmatic aspects of human factors-driven information design. Both successful and failed design examples are included to help readers understand the principles under discussion"--